Diphyllin Shows a Broad-Spectrum Antiviral Activity against Multiple Medically Important Enveloped RNA and DNA Viruses - Štefánik, Michal; Shivajirao Bhosale, Dattatry; Haviernik, Jan; Straková, Petra; Fojtíková, Martina; Dufková, Lucie; Huvarová, Ivana; Salát, Jiří; Bartáček, Jan; Svoboda, Jan; Sedlák, Miloš; Růžek, Daniel; et al. (MDPI, 2022)
Diphyllin is a natural arylnaphtalide lignan extracted from tropical plants of particular importance in traditional Chinese medicine. This compound has been described as a potent inhibitor of vacuolar (H+)ATPases and hence of the endosomal acidification process that is required by numerous enveloped viruses to trigger their respective viral infection cascades after entering host cells by receptor-mediated endocytosis. Accordingly, we report here a revised, updated, and improved synthesis of diphyllin, and demonstrate its antiviral activities against a panel of enveloped viruses from Flaviviridae, Phenuiviridae, Rhabdoviridae, and Herpesviridae families. Diphyllin is not cytotoxic for Vero and BHK-21 cells up to 100 mu M and exerts a sub-micromolar or low-micromolar antiviral activity against tick-borne encephalitis virus, West Nile virus, Zika virus, Rift Valley fever virus, rabies virus, and herpes-simplex virus type 1. Our study shows that diphyllin is a broad-spectrum host cell-targeting antiviral agent that blocks the replication of multiple phylogenetically unrelated enveloped RNA and DNA viruses. In support of this, we also demonstrate that diphyllin is more than just a vacuolar (H+)ATPase inhibitor but may employ other antiviral mechanisms of action to inhibit the replication cycles of those viruses that do not enter host cells by endocytosis followed by low pH-dependent membrane fusion.
Difyllin vykazuje širokospektrální antivirovou aktivitu proti mnoha lékařsky důležitým obaleným RNA a DNA virům
Keywords: enveloped virus; diphyllin; cleistanthin B; vacuolar ATPase inhibitor; antiviral activity; cytotoxicity; obalený virus; difyllin; cleistanthin B; vakuolární inhibitor ATPázy; antivirová aktivita; cytotoxicita